Pharmacokinetics of rabeprazole granules versus tablets, and the effect of food on the pharmacokinetics of rabeprazole granules in healthy adults—cross‐study comparison. Issue 5 (23rd May 2014) - Thyssen, An; Solanki, Bhavna; Gonzalez, Martha; Leitz, Gerhard; Treem, William; Mannaert, Erik
Abstract The primary objective was to compare the pharmacokinetics (PK) of rabeprazole granules versus rabeprazole tablets, and assess the effect of food on the PK of rabeprazole granules. Data from three phase 1, open‐label, single‐dose, randomized, crossover studies in healthy adult participants are presented separately and as a cross‐study comparison; study 1: PK of phase 1 rabeprazole granules versus rabeprazole tablets under fasting conditions; study 2: PK of phase 3 rabeprazole granules versus phase 1 rabeprazole granules; study 3: bioequivalence of to‐be‐marketed rabeprazole granules (sprinkle capsules) versus phase 3 rabeprazole granules; and assessment of the food effect for the to‐be‐marketed rabeprazole granules. Overall, 123 of 130 participants enrolled completed the studies. The overall plasma exposure as measured by area under the plasma concentration–time curve (AUC) was comparable between rabeprazole granules and tablets; mean peak plasma concentration (Cmax) was lower for the granules compared with tablets. The plasma elimination half‐life was short and independent of formulation. Food intake prior to administration of the to‐be‐marketed granules delayed the absorption and reduced the estimated parameters for bioavailability by 55% (Cmax) and 28% (AUCinf). Rabeprazole was well‐tolerated.